2024
DOI: 10.3390/ijms25063180
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Investigation and RNA-seq of KN1 Involved in Leaf Angle Formation in Maize (Zea mays L.)

Yuanming Wu,
Yunfang Zhang,
Zelong Zhuang
et al.

Abstract: Leaf angle (LA) is one of the core agronomic traits of maize, which controls maize yield by affecting planting density. Previous studies have shown that the KN1 gene is closely related to the formation of maize LA, but its specific mechanism has not been fully studied. In this study, phenotype investigation and transcriptomic sequencing were combined to explore the mechanism of LA changes in wild type maize B73 and mutant kn1 under exogenous auxin (IAA) and abscisic acid (ABA) treatment. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Research has revealed that during the initial stages of tissue differentiation, the preligule zone emerges at the junction between the leaf blade and the leaf sheath. Subsequently, the mature lamina joint is established through the ongoing proliferation and differentiation of cells [ 11 ]. The aberration in the lamina joint structure typically involves the inhibition of longitudinal cell elongation in the adaxial region (proximal to the leaf primordium) and an increase in the division of sclerotic cells in the abaxial region (distant from the leaf primordium), consequently resulting in the formation of erect leaves [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has revealed that during the initial stages of tissue differentiation, the preligule zone emerges at the junction between the leaf blade and the leaf sheath. Subsequently, the mature lamina joint is established through the ongoing proliferation and differentiation of cells [ 11 ]. The aberration in the lamina joint structure typically involves the inhibition of longitudinal cell elongation in the adaxial region (proximal to the leaf primordium) and an increase in the division of sclerotic cells in the abaxial region (distant from the leaf primordium), consequently resulting in the formation of erect leaves [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%